2022
DOI: 10.1177/1759720x221116408
|View full text |Cite
|
Sign up to set email alerts
|

Open questions on the management of targeted therapies for the treatment of systemic sclerosis-interstitial lung disease: results of a EUSTAR survey based on a systemic literature review

Abstract: Background: The results of randomized controlled (RCT) and retrospective studies have expanded the armamentarium of drugs for systemic sclerosis (SSc) – interstitial lung disease (ILD) treatment. The correct positioning of these drugs is not yet clarified. Objectives: Systemic literature review (SLR) on rituximab (RTX), tocilizumab (TCZ), nintedanib and abatacept (ABT) for the treatment of SSc-ILD. The results of the SLR were used to create a dedicated survey. Design: The study was performed as a systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…In fact, a recent EUSTAR survey showed how the majority of physicians (88%) expert in treating patients with SSc-ILD consider that NTD should be combined with other immunosuppressive treatments instead of using it as monotherapy. 16 Moreover, it should also be noticed that besides the efficacy in preserving lung function, our study showed that the progressive phenotype (defined according to OMERACT definitions) observed in 60% of our patients could be effectively counteracted in the majority of patients with NTD therapy. This result is particularly important as patients with progressive ILD phenotype, being a significant percentage of the whole population with SSc, 5 are the most difficult to treat.…”
Section: Systemic Sclerosis Systemic Sclerosis Systemic Sclerosismentioning
confidence: 52%
See 1 more Smart Citation
“…In fact, a recent EUSTAR survey showed how the majority of physicians (88%) expert in treating patients with SSc-ILD consider that NTD should be combined with other immunosuppressive treatments instead of using it as monotherapy. 16 Moreover, it should also be noticed that besides the efficacy in preserving lung function, our study showed that the progressive phenotype (defined according to OMERACT definitions) observed in 60% of our patients could be effectively counteracted in the majority of patients with NTD therapy. This result is particularly important as patients with progressive ILD phenotype, being a significant percentage of the whole population with SSc, 5 are the most difficult to treat.…”
Section: Systemic Sclerosis Systemic Sclerosis Systemic Sclerosismentioning
confidence: 52%
“…The combination of NTD with other immunosuppressive drugs is not a novelty. In fact, a recent EUSTAR survey showed how the majority of physicians (88%) expert in treating patients with SSc-ILD consider that NTD should be combined with other immunosuppressive treatments instead of using it as monotherapy 16. Moreover, it should also be noticed that besides the efficacy in preserving lung function, our study showed that the progressive phenotype (defined according to OMERACT definitions) observed in 60% of our patients could be effectively counteracted in the majority of patients with NTD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, several major knowledge gaps have been identified. 68 In our opinion, future research should focus on the practical use of the available drugs to answer specific unmet needs in the therapeutic approach. This would allow us to move beyond expert opinions and compensate for the lack of real evidence on different points with specific strategies, including initiation, combination, and continuation of treatment and monitoring (Box 1).…”
Section: Discussionmentioning
confidence: 99%
“…anti-U11/U12 antibodies are more prevalent in CTP negative patients [ 39 ]. However, this is not only limited to nintedanib, but applies to other novel and alternative treatment approaches in SSc-ILD, including agents with strong-supporting evidence, such as tocilizumab and rituximab [ 55 , 56 ], or others with biological or promising compoundssuch as abatacept, lenabasum, romilkimab, belimumab, bermekimab, brodalumab, tofacitinib, or even rituximab [reviewed in [ 1 , 57 ]].…”
Section: Implication For New Treatment Strategiesmentioning
confidence: 99%